Characteristics and Invitro Digestibility of Kalimantan Swamp Forage as Animal Feed - Rostini, Tintin; Zakir, Irwan; Biyatmoko, Danang (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2024)
This study aims to evaluate swamp forage, for possible application as an animal feed in South Kalimantan Indonesia. The samples were obtained from the swamp areas through a survey method, by collecting sampling the grass from 2 selected regions (North Hulu Sungai and South Hulu Sungai). The observed parameters are 1). Identify the characteristics of the growth of swamp grass by the shape of leaves, roots and flowers. 2). Measurement of Nutrient Content, NDF and ADF, nutrient content of swamp forage.. The results showed that the characteristics of the South Kalimantan swamp grass had stolon and fiber roots, the leaves were mostly ribbon-shaped and compound flowers, and the highest lignin content was in Ischaemum polystachyum grass. J. Presl of 11.45%, total phenol 9.23, tannins of 3.74 and condensed tannins of 1.43. while for the highest digestibility of Hymenachne amplexicaulis (Rudges) Ness grass, namely dry matter digestibility of 31.25%, organic matter 27.42%, VFA 124.22 mM and NH3 of 3.65.mM.. The findings in this study will provide important information about forage fodder that grows in swampland in Kalimantan. It was concluded that swamp grass has a comparative advantage compared to other grasses.